The family competence approach, an experience of socio-educational work with families - Carmen Orte Socias; Lluís Ballester; Martí X March (Sociedad Iberoamericana de Pedagogía Social, 2013)
Introduction. The Spanish adaptation of the Family Competence Program (FCP) offers a way of working socio-educationally with families that need to improve their functionality. The socio-educational methodologies for working with families applied by FCP, through medium term processes (14 weeks), were designed in the framework of the family competence approach, in accordance with rigorous criteria. The correct application of the FCP, according to its contents and methodologies, offers good results proven in primary care social services with families in a difficult situation. Method. Controlled applications of the FCP were conducted, using a quasi-experimental design consisting of a control group and pre-test and post-test measurements. The sample was made up of 217 families which took part in the programme and 14 families that participated in a control group. Validated instruments were applied to carry out the assessments of the methodological processes and the assessments of the families. Results. Positive changes can be observed in six fundamental family factors. The quality of the methodology and fidelity to the FCP in the application obtain excellent results. Methodological and fidelity indicators correlate positively with the results of the families. This relationship can be considered underrated due to the problems present in the families. Discussion. The self-assessments of the participants and of the professionals, even though they were rigorously controlled, may represent a source of bias. In the short term the results may represent an overrating. Either way, the FCP is an excellent socio-educational program for preventive work with families with functional difficulties.